The Effectiveness Of Steam Integrated Approach Using Scratch Module On Achievement And Computational Thinking In Learning Electricity Concepts - Tan, Wee Ling (2022)
This study examined the effectiveness of STEAM (Science, Technology, Engineering, Art, Mathematics) integrated approach via Scratch module in enhancing and retaining achievement, computational thinking (CT) and five subconstructs of CT in learning electricity concepts among 29 male and 30 female Form two secondary school students through Scratch module, which was developed based on ASSURE model. The five subconstructs CT was algorithmic thinking, cooperativity, creativity, critical thinking and problem solving. In this research, a quasi-experimental design was employed with pre-test, post-test and delayed post-test of Electricity Achievement Test (EAT) and Computational Thinking Survey (CTS) to collect the quantitative data. The EAT, which consisted seven structured questions, was utilised to measure the students’ achievement in the electricity concepts while CTS, which consisted twenty nine question on the five subconstruct of CT, was administered to assess the CT and five subconstructs of CT. In the other hand, qualitative data was also collected through the designed animated stories and games on electricity concepts by students at the end of the intervention. The hypotheses were tested based on inferential statistics using Paired Sample T Test, ANCOVA test, MANCOVA test, ANOVA Repeated Measure test and MANCOVA Repeated Measure test.